Undulator-based and crystal-based gamma radiation sources for positron generation; Journal of Physics: Conference Series; Volume 517, № 1 - Potylitsyn A. P. Alexander Petrovich (2014, 2014)
Oriented Si or diamond crystals with thicknesses about 10-20 mm can be considered as an effective «solid-state undulator» if electron energy will be higher than 10 GeV. The scheme where such a crystal (photon radiator) placed upstream of the amorphous positron converter with thickness less than 1 radiation length (hybrid scheme) may provide the intensity of produced and accelerated positrons comparable with an intensity of the initial electron beam. In this case the deposited energy in both parts of the hybrid scheme positron source may be much less than the damage threshold